AGRARIAN RESOURCES BASED LEADERSHIP TRAINING FOR PUCUNG VILLAGE GOVERNMENT OFFICE STAFF - Aristiono Nugroho (RADJA PUBLIKA, 2023)
After having the Masterplan, the Pucung Village Government needs outreach and community awareness activities about important points in the master plan, which are packaged in an activity entitled: